Effect of porcine reproductive and respiratory syndrome virus on subsequent Pasteurella multocida challenge in pigs - Carvalho, LFOS; Segales, J.; Pijoan, C. (Elsevier B.V., 1997)
This trial was conducted to evaluate the effect of Porcine reproductive and respiratory syndrome virus (PRRSv) on a subsequent challenge with Pasteurella multocida in pigs. Sixteen, 3-4 week-old piglets, from a PRRSv and Aujeszky disease virus (ADV) free herd were used. Animals were equally and randomly allocated in four groups which were treated according the following schedule: Group I: negative controls; Group II: inoculation with only PRRSV; Group III: inoculation with PRRSV and P. multocida; Group IV: inoculation with ADV and multocida (positive controls), PRRSV and ADV were inoculated intranasally, at the doses of 10(4.6) and 10(4.5) TCID50/ml, respectively. Five days later, pigs from groups III and IV were inoculated intranasally, with two ml of a 10(9) CFU/mL suspension of equal parts of P. multocida, strains A52 and A24. No lesions were observed in piglets of group I. Microscopically, interstitial pneumonia was identified in all piglets of groups II and III and 3/4 piglets from group IV. Bronchopneumonia was detected in 3/4 of the piglets from group III and in all animals of group TV which, additionally, showed meningo-encephalitis and purulent rhinitis. Macroscopically, only piglets of groups III and IV had lung consolidation. However, much lower pneumonic scores (2.3%) were observed in group III, where 3 of 4 piglets were affected. on the other hand, all piglets of group IV showed some degree of pulmonary consolidation, with a mean score of 13.7%. Based on these results, it appears that the role of PRRSV as a initiator of secondary diseases is still undefined, but is probably mild, There was no clear interaction between PRRSV and Pasteurella multocida under the conditions and strains tested here. (C) 1997 Elsevier B.V. B.V.
Keywords: PRRSv; P-multocida; interaction; ADV; pneumonia